Watching narratives of travel-as-transformation in The Beach and The Motorcycle Diaries - Sampaio, S. (2014)
The attention recently accorded to feature films in tourism studies has been mostly driven by the idea that cinema has the ability to provoke in the viewer a sense of anticipation regarding a given or potential tourist destination. Films, however, also play an important role in shaping our notions of what a tourist experience should be. One of the most common tropes in travel or tourism-related films has been the trope of the journey as a transformative or ‘life-changing experience’. This paper explores the connections between this recurrent trope and the classical narrative film. Broadly consisting of a character-centred narrative in which events are organised by causal logic, moving towards the resolution of an initial problem or crisis, the classical narrative film relies heavily upon the idea of change (the turning point which prepares the way for denouement) and is, therefore, particularly prone to depictions of tourism as a life-changing experience. Despite innovations introduced from the 1960s onwards, most mainstream travel films still follow this narrative scheme. This paper analyses two of these films, The Beach (2000, dir. Danny Boyle) and The Motorcycle Diaries (2004, dir. Walter Salles), which have been widely discussed in relation to tourism, underlining how they support notions of travelling as a source of transformation, sidestepping more banal kinds of experiences. Drawing on a large sample of online film reviews, I argue that viewers are not unaware of this bias, which they often reproduce, comment upon and challenge.